Association Between Diet Quality and Prevalence of Obesity, Dyslipidemia, and Insulin Resistance Among Filipino Immigrant Women in Korea: The Filipino Women's Diet and Health Study - Kim, Hee Sun; Lee, Heejin; Provido, Sherlyn Mae P.; Kang, Minji; Chung, Grace H.; Hong, Sangmo; Yu, Sung Hoon; Lee, Chang Beom; Lee, Jung Eun (Frontiers in Public Health, 2021)
Objectives Diet quality may be a key modifiable factor for the prevention of non-communicable disease. We aimed to investigate the association between diet quality and prevalence of obesity, dyslipidemia, and insulin resistance among Filipino immigrant women in Korea. Methods A total of 413 participants from 2014–2016 baseline population of the Filipino Women’s Diet and Health Study (FiLWHEL) were examined. Individual dietary intakes were evaluated through 24-hour recalls, and then converted into two dietary quality assessments; Minimum Dietary Diversity for Women (MDD-W) developed by the Food and Agriculture Organization (FAO), and the Data Derived Inflammation Index (DDII) originally developed by our group. Fasting blood levels of triglycerides, high-density lipoprotein cholesterols, glucose, and insulin were measured. We used logistic regression models for odds ratios (ORs) with 95% confidence intervals (CIs). Results We found a statistically significant association between MDD-W scores and decreased prevalence of abdominal obesity; ORs (95% CIs) of the 3rd vs 1st tertiles were 0.58 (0.36 - 0.94 ; p for trend = 0.029). Increased DDII was associated with elevated prevalence of dyslipidemia and insulin resistance; ORs (95% CIs) of the 5th vs 1-3rd quintiles were 6.44 (2.56 - 16.20) for triglycerides (TG), 3.90 (1.92 - 7.90) for low density lipoprotein (LDL) cholesterols, 3.36 (1.81 - 6.24) for total cholesterols (TC), 6.25 (2.53 - 15.41) for abnormal TG/HDL ratios, 3.59 (1.96 - 6.59) for HbA1c, 2.61 (1.11 - 6.17) for fasting blood glucose levels, 9.67 (4.16 - 22.48) for insulin levels, and 9.73 (4.46 - 21.25) for homeostasis model assessment of insulin resistance (HOMA-IR) (p for trend <0.001 for all, except 0.033 for fasting blood glucose). Conclusions Greater dietary diversity was inversely associated with prevalence of abdominal obesity in Filipino immigrant women. Pro-inflammatory scores based on diet and lifestyle factors were associated with increased prevalence of dyslipidemia and insulin resistance. Further epidemiological studies on the relationship between dietary acculturation and chronic disease are warranted.